Wireless Sensor Networks for Developing Countries First International Conference, WSN4DC, Jamshoro, Pakistan, April 24-26, 2013, Revised Selected Papers - Shaikh, Faisal Karim; Chowdhry, Bhawani Shankar; Ammari, Habib M.; Uqaili, Muhammad Aslam; Shah, Assadullah; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the First International Conference on Wireless Sensor Networks for Developing Countries, WSN4DC 2013, held in Jamshoro, Pakistan, in April 2013. The 10 revised full papers presented were carefully reviewed and selected from 30 submissions. The papers are organized in topical sections on WSN applications/services for developing countries; mobile WSN; underwater WSN; VANETS; body area networks; energy harvesting in WSN; WSN and cloud integration; WSN and IoT; QoS and Qot; WSN MAC, network and transport protocols; cross layer approaches; security aspects in WSN; WSN applications in smart grid and energy management; WSN in structural health monitoring.
WSN applications/services for developing countries -- Mobile WSN -- Underwater WSN -- VANETS -- Body area networks -- Energy harvesting in WSN -- WSN and cloud integration -- WSN and IoT -- QoS and Qot -- WSN MAC, network and transport protocols -- Cross layer approaches -- Security aspects in WSN -- WSN applications in smart grid and energy management -- WSN in structural health monitoring.
Keywords: Computer science; Computer communication systems; Software engineering; Algorithms; Information storage and retrieval; Artificial intelligence; Computer Science; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Information Storage and Retrieval; Software Engineering; Electronic books